The Macmillan visual dictionary - Corbeil, Jean Claude; Archambault, Ariane (Macmillan, 1995)
One of the most extraordinary reference titles ever produced is now available in paperback!Since its publication in 1992, The Macmillan Visual Dictionary has been heralded as the most innovative and graphically stunning reference work of its kind. And this remarkable volume certainly merits the praise: it provides full-color visual definitions of nearly everything.Want to know the difference between curly endive and curled kale? Curious about the distinguishing features of various judo holds and throws? Wondering what each and every feature of a Gothic cathedral is called? The answers to these and thousands of other questions are at your fingertips.The Macmillan Visual Dictionary identifies more than 25,000 terms with more than 3,500 full-color illustrations covering 600 subjects. Ranging from Astronomy and Geography to Combat Sports and Communications, from the Vegetable and Animal Kingdoms to Human Beings and Symbols, and from Architecture and House Furniture to Maritime Transport and Energy, the book's 28 chapters provide truly exhaustive coverage of the world as we know it. A usage guide, detailed table of contents, and extensive index allow for easy referencing.As ideal for the family reference library as for the casual browser trying to identify that "whatchamacallit", the compact paperback edition of The Macmillan Visual Dictionary will continue to set the standard in reference works.